Palaeoenvironmental conditions during MIS 6/MIS 5 transition recorded in speleothems from the Tatra Mountains. (28th September 2020) - Pawlak, Jacek; Błaszczyk, Marcin; Hercman, Helena; Matoušková, Šárka
Abstract : We present 100‐ka multiproxy palaeoenvironmental records from three stalagmites collected in different caves located in the Tatra Mountains on the Polish/Slovakian border. A combination of three records from one mountain region helps to estimate local factors controlling the recorded proxies and separate them from regional/global patterns. The studied stalagmites react to the same environmental changes in different ways due to the differences in their local settings. Furthermore, the analysed records show environmental changes from relatively cold and dry climates to interglacial conditions of MIS 5e. One episode of a colder climate during the MIS 6/MIS 5e transition similar to Dryas periods is observed in all studied stalagmites. The δ 18 O record from the MAG‐1 stalagmite is most similar to the GRIP record. During the MIS 5e, the δ 18 O record from the MAG‐1 stalagmite e xhibits a pattern similar to the records from the western part of the European continent. This finding suggests that the Atlantic Ocean was an important source of moisture for the region. The observed rapid change of δ 18 O, δ 13 C, Sr and Si proxies from the MAG‐1 and Dz‐1 stalagmites after 109 ka are potentially related to a drier and colder climate.